α-Adrenoceptor-mediated prejunctional effects of chloroethylclonidine in the canine saphenous vein - Guimarães, Serafim; Paiva, Maria Q.; Pereira, Oduvaldo [UNESP] (My University, 1997)
The present study was undertaken to look for the effect of chloroethylclonidine (CEC) on prejunctional alpha-2 autoreceptors of the canine saphenous vein. The effect was tested on tritium overflow evoked by electrical stimulation from tissues preloaded with 0.2 μM 3H- norepinephrine. Yohimbine (3-300 nM) and CEC (1-125 μM) increased and UK- 14,304 reduced the overflow of tritium evoked by 300 pulses (1 Hz). The maximal increase of tritium overflow caused by yohimbine was much higher than that caused by CEC: 3.82 and 1.74 times, respectively. CEC (5 μM) abolished both the inhibition caused by UK-14,304 and the enhancement of tritium overflow caused by yohimbine. However, when CEC was added after yohimbine, it reduced the electrically evoked overflow of tritium, the maximal effect being a reduction of tritium overflow by 35%. Prazosin (1-100 nM) did not change either the inhibitory effect of UK-14,304 or the facilitatory effect of CEC. These results suggest that CEC acts on two different subtypes of prejunctional alpha-2 autoreceptors; on one of them it acts as an antagonist and increases the electrically evoked overflow of tritium (and inhibits both the effect of UK-14,304 and yohimbine); on the other it acts as an agonist and reduces the electrically evoked overflow of tritium. Alternatively, one can admit that CEC is able to inhibit alpha-2 autoreceptors, which causes an increase of the transmitter release, and to activate a nonadrenergic inhibitory receptor thus causing a reduction of the transmitter release.
Keywords: alpha adrenergic receptor; brimonidine; chloroethylclonidine; tritium; yohimbine; animal tissue; controlled study; dog; drug effect; drug mechanism; electrostimulation therapy; evoked response; female; male; neurotransmission; nonhuman; presynaptic nerve; priority journal; saphenous vein; Adrenergic alpha-Antagonists; Animals; Autoreceptors; Clonidine; Dogs; Dose-Response Relationship, Drug; Female; Male; Prazosin; Quinoxalines; Receptors, Adrenergic, alpha-2; Saphenous Vein; Yohimbine